The Study of the Role and Work of the School Transition Responsible Person in Supporting Students with Special Educational Needs - Dzamukashvili, Shorena; Mikeladze, Tamar ("Intercultural Dialogues" Transactions, 2023)
The transition period can be a source of stress and concern for families with children who have special needs, particularly when there is limited support from schools or kindergartens. Teachers, too, may experience anxiety and uncertainty when faced with these processes, often due to encountering various obstacles and not knowing how to effectively assist diverse students in their classrooms. To ensure the transition process for students with special educational needs is as seamless as possible, schools must implement a well-designed transition promotion program and specific support measures. This study investigates the attitudes and actions of individuals responsible for facilitating school transitions and assesses their role in the process for students with special educational needs. The research took place in 2022-2023 as part of the "Study of the Transition of SEN Children to School (within Telavi Municipality)" project conducted by the Faculty of Education Sciences at Iakob Gogebashvili Telavi State University. This project was part of the UNICEF initiative "Development of Monitoring Capabilities of State Universities for the Children of the Parliament of Georgia to Facilitate Informed Decision-Making and Research." The study findings revealed that the transition process for students with special needs in schools is often not as effective as desired. In light of these findings, it is recommended that school staff involved in these transitions undergo retraining. Additionally, although schools commonly assign the role of transition coordinator to a special education teacher based on their experience, it was also observed that the classroom environment lacks the necessary resources, and there is a lack of systematic cooperation among the parties involved in the transition process.